Management Strategies for Birds and Wild Animals in Organic Crop Production - Rao, V. Vasudeva (International Journal of Economic Plants, 2015)
The organic farming in real sense envisages a comprehensive management approach to improve the health of underlying productivity of the soil. On the other hand organic agriculture is a production system which avoids or largely excludes the use of synthetic compounded fertilisers, pesticides, growth regulators and livestock feed additives. It relies on crop rotation, crop residues, animal manure, legumes, green manure, off farming organic waste and aspects of biological pest control. The crop production in general affected through various insect pests, plant diseases, and weed plants to a greater extent in different stages of crop in anyway neither inorganic nor organic farming. In recent times, apart from the above pest and diseases, avian fauna mainly consisting of depredatory birds and mammals with special reference to rodents, wild boars, blue bull and monkeys started gaining pest status and in certain cases a huge damage is being encountered due to some of these vertebrate pests. Among them, depredatory birds and wild boar has become regular menace for farmers in major crops resulting into enormous crop damages. The present study focused to evaluate various cost-effective management strategies to minimize the damage caused by vertebrate pests and also to minimize man-animal conflict in agricultural landscape.